Breast cancer and occupation: Non-parametric and parametric net survival analyses among Swiss women (1990–2014) - Guseva Canu, Irina; Bovio, Nicolas; Arveux, Patrick; Bulliard, Jean-Luc; Fournier, Evelyne; Germann, Simon; Konzelmann, Isabelle; Maspoli, Manuela; Rapiti, Elisabetta; Grzebyk, Michel (Frontiers in Public Health, 2023)
Introduction: Occupation and socio-economic status may both contribute to differences in risk and stage at diagnosis of breast cancer. We aimed at determining whether occupation, skill level required for the occupation and the socio-professional category affect the breast cancer survival (BCS) up to 10 years after diagnosis. Material and Methods: We used cancer registry records to identify women diagnosed with primary invasive breast cancer between 1990 and 2014 in western Switzerland and matched them with the Swiss National Cohort. The effect of work-related variables on BCS was assessed using non-parametric and parametric net survival methods. Results: Study sample included 8,678 women. In the non-parametric analysis, we observed a statistically significant effect of all work-related variables on BCS. Women in elementary occupations, with low skill level, and in paid employment not classified elsewhere, had the lowest BCS, while professionals, those with the highest skill level and belonging to top management and independent profession category had the highest BCS. The parametric analysis confirmed this pattern. Considering elementary occupations as reference, all occupations but Craft and related trades had a hazard ratio (HR) below 1. Among professionals, technicians and associate professionals, and clerks, the protective effect of occupation was statistically significant and remained unchanged after adjustment for age, calendar period, registry, nationality and histological type. After adjusting for tumor stage, the HRs increased only slightly, though turned non-significant. The same effect was observed in top management and independent professions and supervisors/low level management and skilled laborers, compared to unskilled employees. Conclusion: These results suggest that work-related factors may affect BCS. As this study was conducted using a relatively small sample and limited set of covariates, further larger studies are required for more detailed analyses of at risk occupations and working conditions and assessing the potential interaction between work-related variables and tumor stage.